2012
DOI: 10.1016/j.jcrs.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Modulation transfer function and optical quality after bilateral implantation of a +3.00 D versus a +4.00 D multifocal intraocular lens

Abstract: PURPOSE:To determine whether the improvement in intermediate vision after bilateral implantation of an aspheric multifocal intraocular lens (IOL) with a C3.00 diopter (D) addition (add) occurs at the expense of optical quality compared with the previous model with a C4.00 D add.SETTING: Department of Ophthalmology, University of São Paulo, São Paulo, Brazil. DESIGN:Prospective randomized double-masked comparative clinical trial. METHODS:One year after bilateral implantation of Acrysof Restor SN6AD1 C3.00 D IOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Because of their double coaxial optics, multifocal IOLs provide lower optical quality as compar ed with monofocal IOLs [19]. Studies conduct ed with HartmannShack aberrometers demons trated complex pathways especially of spherical aberration that may be positive for smaller aper ture diameters, and negative for larger, reduc ing pointspread function [20].…”
Section: Optical Quality With Multifocal Intraocular Lensesmentioning
confidence: 99%
“…Because of their double coaxial optics, multifocal IOLs provide lower optical quality as compar ed with monofocal IOLs [19]. Studies conduct ed with HartmannShack aberrometers demons trated complex pathways especially of spherical aberration that may be positive for smaller aper ture diameters, and negative for larger, reduc ing pointspread function [20].…”
Section: Optical Quality With Multifocal Intraocular Lensesmentioning
confidence: 99%
“…It has been suggested that the MTF plots are associated with the subsystems that make up a complete electro-optical or photographic system [22]. The MTF is associated with tear film stability [23] or the type of intraocular lens [24]. The OSI is defined as the ratio between the integrated light intensity in the periphery and that around the central peak of the double-pass image [11].…”
Section: Discussionmentioning
confidence: 99%
“…The Strehl ratio expresses the ability of the eye to form a point image on the retina when a point object is seen [28]. It is related to wavefront errors [29], aging [17] and characteristics of the intraocular lens [24]. …”
Section: Discussionmentioning
confidence: 99%
“…This lens provides better intermediate vision than the +4 model with no evident change in visual disturbances. The preferred reading distance for the +3 lens was near 40 cm, whereas with the +4 add the preferred reading distance was about 32 cm 3,4…”
Section: Introductionmentioning
confidence: 99%